Gender and power in families - Perelberg, Rosine Jozef; Miller, Ann C. (Karnac, 2011)
Annotation Behind the systems approach to the family lie the hidden assumptions that men and women are equal within the family structure and that women and men are treated equally in clinical practice. Gender and Power in Familieschallenges these assumptions, presenting both a conceptual discussion of the subject and a review of the clinical practice. The contributors, all experienced therapists who work with women in a variety of public health and social service settings, re-examine the position of women and men in families and in family therapy. Drawing on their work with women from varied social amd ethnic backgrounds, the authors look at the issues as they relate to women who have suffered sexual abuse as children, and women struggling to bring up children alone or with partners with whom they are in perpetual conflict. They also explore the problems of women who are deemed mentally handicapped, women who are first-generation immigrants, and black women, who are marginalized and oppressed by race and class combined with gender. Gender and Power in Familieslooks closely at the family in its wider social context, arguing that the issues of gender and power are central to family therapy, training and practice.